2016
DOI: 10.1016/j.ijom.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trauma and surgical treatment on the quality of life of patients with facial fractures

Abstract: This study assessed the impact of oral and maxillofacial trauma and surgical treatment on the quality of life of patients. The study included 66 patients (age range 18-65 years) with facial fractures; 33 required surgical treatment and 33 required conservative (non-surgical) treatment. Quality of life was evaluated by applying the Oral Health Impact Profile questionnaire (OHIP-14) immediately after diagnosis of the trauma (T1), 30 days after surgery or trauma (T2), and 90 days after surgery or trauma (T3). For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 21 publications
5
37
0
7
Order By: Relevance
“…An assessment with the same research tool was carried out by Conforte et al in a group of patients with craniofacial injuries, immediately after trauma, and then 30 and 60 days later. 16 The present findings corroborate those reported by Conforte et al, who also observed time-related improvements in the quality of life after mandibular fractures.…”
Section: Discussionsupporting
confidence: 93%
“…An assessment with the same research tool was carried out by Conforte et al in a group of patients with craniofacial injuries, immediately after trauma, and then 30 and 60 days later. 16 The present findings corroborate those reported by Conforte et al, who also observed time-related improvements in the quality of life after mandibular fractures.…”
Section: Discussionsupporting
confidence: 93%
“…Diagnostic accuracy together with type and timing of treatments significantly affect the clinical evolution of such traumas, allowing to improve functional results and limit cosmetic damages. Interestingly, the severity of maxillofacial injuries may be considerable, and can divert clinicians' attention from other concomitant injuries that are less evident but potentially life-threatening 10, 11, 12, 13. The aim of this study was to find out the concomitant injuries in patients admitted for maxillofacial traumas to the Emergency Department (ED) of the University Hospital Messina (North-East Sicily, Italy).…”
Section: Introductionmentioning
confidence: 99%
“…There is presently a lack of data regarding physical and psychological impairment in such injuries, 4,[9][10][11] but health-related quality of life (HRQOL) protocols after facial trauma have been well recognized and adopted. 4,[12][13][14] The main purpose of the current study was to compare the 36-Item Short Form Health Survey (SF-36) scores of surgically treated maxillary and zygomatic fractures in male patients with the reported normative data of SF-36 for the Croatian population. The secondary aim was to correlate important clinical variables with different concepts of the SF-36.…”
Section: Introductionmentioning
confidence: 99%